Establishment of HACCP System for raw unclean edible Bird’s Nest processing plant in Malaysia - Tay, Guo Xuan; Mas Nordiana Rusli,; Khairul Anuar Mohd Ali,; Zainol Mustafa, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The focus of the study is on the establishment of HACCP system for raw unclean edible bird’s nest (RUC EBN) processing plant in Malaysia. Exploratory hazard analysis was applied to examine and prognose the possible failure modes in processing of raw unclean EBN based on characteristics, purpose or the interaction of processes where the system affixed to. Critical Control Points were determined and administered in the Ishikawa diagram. Deployment of the Ishikawa diagram is to discover the major causes that lead to failure in the heat treatment process. Application of cause-and-effect diagram ascends us to promising results which validate and verify outcomes attained from Failure Mode and Effect Analysis (FMEA). Risk assessment outputs from FMEA and food safety hazard matrix were compared concurrently. FMEA is deployed as part of risk assessment in Hazard Analysis and Critical Control Point (HACCP) system of raw unclean edible bird’s nest processing. Enrollment of FMEA within Food Safety Management System (FSMS) contribute to a more definite qualitative assessment where rapid preventive or corrective intercession is possible.